Sperm characteristics in frozen semen using microscopy and flow cytometry in breeding bulls from Cajamarca, Peru. - Rafael-Bautista, J. (2025)
Evaluating bulls is crucial for selecting sires and ensuring the sustainability of livestock herds. This study aimed to assess sperm quality in frozen semen from breeding bulls in Cajamarca, Peru. Three bulls from the Holstein, Brown Swiss, and Fleckvieh breeds were selected, and three 0.5 mL straws from each bull were analyzed. Optical microscopy revealed an overall motility of 40.37±18.29%, a concentration of 89.07±39.51 million spermatozoa/mL, and normal morphology of 81±5.95%, surpassing the minimum international quality control standards for commercialization. Flow cytometry analysis showed that plasma membrane integrity (PMI), assessed using SYBR/PI, reached 17.5±7.79%; mitochondrial membrane potential (MMP), evaluated with MitoTracker Deep Red FM, was 22.67±8.96%; and acrosomal membrane integrity (AMI), assessed with FITC-PSA/PI, was 19.24±8.15%. PMI varied among breeds, being lowest in Holstein bulls (11.50±5.32%), followed by Brown Swiss (20.49±9.57%) and Fleckvieh (20.52±4.05%). A similar trend was observed for MMP, with Holstein exhibiting the lowest values (16.01±8.25%), followed by Brown Swiss (23.80±8.9%) and Fleckvieh (28.19±5.28%) (P<0.05). No differences in AMI were found among breeds (P>0.05). A direct correlation was observed between PMI and MMP (r= 0.763; P=0.000), PMI and AMI (r= 0.850; P=0.000), and MMP and AMI (r= 0.635; P=0.000). Normal sperm morphology was correlated with PMI (r= 0.4; P=0.039) and inversely correlated with AMI (r=-0.534; P=0.004). In summary, sperm characteristics assessed via microscopy in breeding bulls from Cajamarca showed acceptable values. However, flow cytometry evaluations revealed lower values, particularly in Holstein bulls, which exhibited lower percentages of PMI and MMP compared to Brown Swiss and Fleckvieh breeds.